2007
DOI: 10.1109/lgrs.2007.900687
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Forest Emissivity at L-Band and a Comparison With Multitemporal Measurements

Abstract: This letter describes recent advances in modeling forest emissivity at L-band. The formulation is based on a previously developed discrete model and includes a new representation of forest litter. Comparisons with multitemporal radiometric data collected in the framework of the "Bray 2004" experiment, which was carried out within Les Landes forest, are shown and discussed. Input variables are given by using detailed ground measurements. In general, the model reproduces both absolute values and temporal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 8 publications
(17 reference statements)
1
28
0
Order By: Relevance
“…It is well known that the presence of vegetation reduces the sensitivity of the microwave measurements to the soil moisture but, since vegetation attenuation increases as wavelength decreases, longer wavelengths are preferred for soil moisture studies [Jackson and Schmugge, 1991]. In view of the availability of the ESA Soil Moisture and Ocean Salinity (SMOS) radiometer and dissemination of its data, several works began to prove the effectiveness of L-band radiometry [Ferrazzoli et al, 2002;Della Vecchia et al, 2007;, which has been shown to have a good sensitivity to soil moisture variations. However, ground based experiments at L-band did not give a definite indication about soil moisture sensitivity in forested areas: some works reported low effects , while others showed moderate sensitivity [Santi et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the presence of vegetation reduces the sensitivity of the microwave measurements to the soil moisture but, since vegetation attenuation increases as wavelength decreases, longer wavelengths are preferred for soil moisture studies [Jackson and Schmugge, 1991]. In view of the availability of the ESA Soil Moisture and Ocean Salinity (SMOS) radiometer and dissemination of its data, several works began to prove the effectiveness of L-band radiometry [Ferrazzoli et al, 2002;Della Vecchia et al, 2007;, which has been shown to have a good sensitivity to soil moisture variations. However, ground based experiments at L-band did not give a definite indication about soil moisture sensitivity in forested areas: some works reported low effects , while others showed moderate sensitivity [Santi et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…As explained in Section 6.2.4, the soil-litter medium is considered a homogenous half-space with a permittivity depending on soil and litter permittivity. However, Della Vecchia et al (2007) found that the resulting soil-litter permittivity is lower than that of the soil and it is less sensitive to soil moisture variations. When the litter effect is removed, the Tor Vergata model simulates a decrease of approximately 13 K from 7 to 12 May in V polarization, similar to what observed by AMSR-E.…”
Section: Model Calibration Over 2009 Datamentioning
confidence: 98%
“…The module was initially developed for forest litter (Della Vecchia et al 2007), but it was adapted to the case of grassland litter in this study. This module represents the litter as a mixture of air and dielectric material overlaying the soil.…”
Section: The Tor Vergata Modelmentioning
confidence: 99%
See 2 more Smart Citations